E-Procurement Implication on The Budgets Absorption in Indonesian Local Government (East Java Provincial Government Cases) - Puji Nurhayati; Djuminah Djuminah (AFEBI Accounting Review, 2017)
Utilization of e-procurement technology in government is very important to achieve accelerated implementation of National and Local Budget that should be indicated in the absence of budget accumulation at the end of the year. The purpose of this study is to examine the effect of the use of e-procurement technology on budget absorption through the practice of procurement of goods / services and procurement performance of goods / services. This study uses primary and secondary data. The sample of this research was 71 units of Local Government Work Unit (SKPD) in East Java Provincial Government. The results show that the utilization of e-procurement technology has a positive effect on budget absorption through the practice of procurement of goods/services. Utilization of e-procurement technology negatively affect the practice of procurement of goods/services and procurement performance of goods/services. Utilization of e-procurement technology negatively affect the performance of procurement of goods/services through the practice of procurement of goods/services. However, the use of e-procurement technology has no effect on budget absorption and has no effect on budget absorption through procurement performance of goods/services because of the attitude of the technology users who are reluctant in the utilization of e-procurement technology.Keywords: e-Procurement, Budget Absorption, Goods/Services Procurement Practice, Procurement Performance of Goods/Services, Utilization of e-Procurement Technology